A SURVEY OF TEACHERS’ PERCEPTIONS ON PROBLEM BASED LEARNING USING ZOOM APP FOR STUDENTS’ SPEAKING SKILL DURING COVID-19 OUTBREAK - Eko Subakti (Graduate Program, University of Islam Malang, 2021)
Abstract Online platform likes a zoom app can be a medium that help the learning process of English run easier in a long distant class. The aims of this study is to find out the teachers’ perceptions on problem-based learning using zoom app for students’ speaking skill during covid-19 outbreak. The research method was a survey, the population were the teachers of Junior High School and Senior High School around East Java and the data were taken from the teachers who had experiences in implementing problem based learning strategy for students’ speaking skill by practicing zoom app as the medium in distance class process. The researcher needed around forty teachers around East Java for taking a part in contributing the data in questionaire. The data were gathered from the questionnaire and then analyzed quantitatively then presented in the form of grafical and table. The result of the research, from 40 respondents, there were 50% of the respondents knew about the characteristics of PBL, 43.21 % of them felt easy and comfortable to apply zoom app as a distance teaching and learning process, especially for students’ speaking skill, 49.58% agreed that zoom app provided advantages for students’ speaking skill by using PBL strategy, 48.57% of them agreed that communication and interaction in speaking class by using PBL strategy via zoom app could run well and gave positive impact for students’ speaking skill, 46.43% respondents stated agree that the teachers felt satisfied in implementing PBL strategy for students’ speaking skill by using zoom app. By this research, it reveals that a big parts of the teachers give a good perception at implementation of Problem-Based Learning (PBL) strategy for students’ speaking skill by using zoom app during covid-19 outbreak. This strategy can be applied well in improving the students’ speaking skill as long as a distance class and in a covid-19 pandemic situation. Keywords: Teachers’ Perceptions’, Problem based learning strategy, Students’ speaking skill, Covid-19 outbreak